Enkulturasi Hukum: Pemberian Mahar Hewan Kerbau dalam Perkawinan - Ali Maskur; Mahsun Mahsun; Mashudi Mashudi; Khoirotin Nisa; Mustla Sofyan Tasfiq (Universitas Wahid Hasyim Semarang, 2022)
Mahar is not a necessary component of marriage, but its presence is required. Marriage Law No. 1 of 1974, KHI, and Islamic Law do not address mahar in detail. Community customs are frequently used as a benchmark in determining mahar, as long as they do not conflict with national or Islamic law. In Kudus area, the provision of mahar in valuables form and as a source of initial livelihood is manifested in the form of buffalo. Throughout its history, this mahar's gift has ranged from no provision to a buffalo of unknown origin. This qualitative-empirical study in Kudus area will investigate the philosophical significance of choosing a buffalo as a marriage mahar as well as the process of law enculturation in society. The philosophical basis for selecting a buffalo is that it represents a powerful animal at work and can be used as livestock to sustain life. Because of changing times, animals are no longer able to fulfill people's desires as working animals and sources of income; the shift in changing the marriage mahar from animals to motorbikes is a new alternative form and an unavoidable choice in responding to the challenges of changing times. Keywords: Legal Enculturation; Mahar; Animal; Motorcycle; Marriage Mahar bukan rukun perkawinan tetapi keberadaannya wajib ada. Undang-undang Perkawinan No 1 tahun 1974, KHI dan Hukum Islam tidak mengatur secara detail tentang mahar. Adat kebiasaan yang ada dimasyarakat seringkali dijadikan patokan dalam penentuan mahar selama tidak bertentang dengan hukum nasional dan hukum Islam. Ketentuan mahar berupa barang berharga dan sebagai bentuk nafkah awal diwujudkan dalam bentuk hewan kerbau di daerah Kudus. Dalam sejarahnya pemberian mahar ini berubah dari tidak tidak ada ketentuan menjadi kerbau tidak diketahui asal usulnya. Penelitian kualitatif-empiris didaerah Kudus ini akan melihat makna filosofis dipilihnya hewan kerbau sebagai mahar perkawinan dan proses enkulturasi hukum di masyarakat. Dasar filosofis dipilihnya hewan kerbau adalah sebagai simbol hewan yang kuat dalam bekerja dan dapat dijadikan hewan ternak untuk menopang kehidupan. Perubahan zaman menjadikan hewan tidak lagi mampu memenuhi keinginan masyarakat sebagai hewan pekerja dan menopang penghasilan, pergeseran merubah mahar perkawinan hewan ke motor merupakan bentuk alternatif baru dan pilihan yang tidak bisa dielakkan dalam menjawab tantangan perubahan. Kata kunci: Enkulturasi Hukum; Mahar; Hewan; Motor; Perkawinan